Laser spot measurement using simple devices - Bonnett Del Alamo M. (2021)
The authors gratefully acknowledge the Dirección de Gestión de la Investigación (DGI-PUCP) for funding under Grant No. DGI-2019-3-0044. C.S. acknowledges support from the Peruvian National Council for Science, Technology and Technological Innovation scholarship under Grant No. 236-2015-FONDECyT. We would also wish to thank R. Sanchez from the Applied Optics Group and the Quantum Optics Group for letting us use their lasers and equipment, as well as Y. Coello for the photodiode. We also thank J. A. Guerra for useful discussions and suggestions.